Indigenous Languages and English in the Globalised Modern Era in Brunei Darussalam (KEMANUSIAAN The Asian Journal of Humanities, 2020)
This article considers two aspects of the linguistic situation in Brunei Darussalam in the globalised modern era: the situation with regard to minority indigenous languages: and the emergent status of Brunei English. Minority languages are threatened with extinction throughout the world and those in Brunei are no exception. There are seven officially recognised indigenous groups, each with its own language, though these are sometimes all claimed to be dialects of Malay—Brunei Malay, Kedayan, Dusun, Bisaya, Tutong, Belait and Murut—but all these languages apart from Brunei Malay are under threat, even though some efforts are currently being undertaken to preserve them. English is also widely spoken in Brunei and Brunei English has features that make it distinct from other Englishes in the world. Some of these features are shared by other regional varieties of English and others are unique to Brunei. The article therefore, analyses the status of the minority languages of Brunei, describes efforts to preserve them and also evaluates the developing status of Brunei English as it evolves under the influences of globalisation; and it finally reflects on problems with neat classification into distinct languages.